The black hole solutions: 1916-1965 - Almeida, Carla Rodrigues (Cadernos de Astronomia, 2023)
Historically, general relativity's first solutions were not recognized as black-holes solutions. They were, a priori, derived to describe the gravitational field of a spherically symmetric massive objects, such as the Sun or an electron. In this paper, I present the black-hole solutions in their historical context, revealing how our understanding of the universe has changed as we discovered fundamental properties of these gravitational fields. My goal is to present a historical introduction to general relativity and black holes, focusing on the theory of gravitation and its interpretations, as didactic support for those who want to initiate their studies on the subject.
Keywords: invisible stars; Massenpunktes; black hole; Schwarzschild; Reissner-Nordström; Kerr; Newman; analytical extensions